2010
DOI: 10.1111/j.1096-0031.2010.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular evidence converge upon a robust phylogeny of the megadiverse Holometabola

Abstract: We present the largest morphological character set ever compiled for Holometabola. This was made possible through an optimized acquisition of data. Based on our analyses and recently published hypotheses based on molecular data, we discuss higherlevel phylogeny and evolutionary changes. We comment on the information content of different character systems and discuss the role of morphology in the age of phylogenomics. Microcomputer tomography in combination with other techniques proved highly efficient for acqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
211
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 155 publications
(229 citation statements)
references
References 70 publications
17
211
1
Order By: Relevance
“…A recent phylogenomic analysis provided a highly resolved insect phylogeny, which is in general overall agreement with morphologically derived phylogenies (e.g. Beutel et al 2011;Yoshizawa 2011). The most significant conflict between morphology and phylogenomics concerns the monophyly of the Paraneoptera; phylogenomics places Psocodea as sister group of Holometabola , whereas morphological analysis places Psocodea as sister to Condylognatha (Yoshizawa & Saigusa 2001;Friedemann et al 2014;Beutel et al 2014).…”
Section: Introductionmentioning
confidence: 68%
“…A recent phylogenomic analysis provided a highly resolved insect phylogeny, which is in general overall agreement with morphologically derived phylogenies (e.g. Beutel et al 2011;Yoshizawa 2011). The most significant conflict between morphology and phylogenomics concerns the monophyly of the Paraneoptera; phylogenomics places Psocodea as sister group of Holometabola , whereas morphological analysis places Psocodea as sister to Condylognatha (Yoshizawa & Saigusa 2001;Friedemann et al 2014;Beutel et al 2014).…”
Section: Introductionmentioning
confidence: 68%
“…Béthoux (2009) assigned these specimens to Coleoptera based exclusively on one feature of inter-veinal network formed from the wing membrane: the presence of rows of angular cells parallel to the principal veins and flanking the intercalary pseudo-veins. No apomorphic features of Coleoptera are mentioned from those listed by Beutel & Haas (2000) or Beutel et al (2008), and no wing organ apomorphies suggested by Kukalová-Peck & Lawrence (2004) for Coleopterida (Coleoptera + Strepsiptera) (Wiegmann et al, 2009;Beutel et al, 2011) are present.…”
Section: Introductionmentioning
confidence: 99%
“…Both beetles and neuropteroids were polyphyletic, owing to contamination. The paper is best remembered for its recovery of Halteria, a hypothesis that they would vigorously defend [74,164 -167] until morphology [48,168] and additional genes [47,154,169,170] overturned it 15 years after it had been proposed.…”
Section: The Problem With 'The Strepsiptera Problem': 1995-2010mentioning
confidence: 99%
“…More recently, the palaeoentomologist Alexandr P. Rasnitsyn described approximately 250 new genera and over 800 new species of fossil insects. He suggested a sistergroup relationship between Hymenoptera (sawflies, bees, wasps and ants) and the remaining Holometabola [43] before this was established with formal analyses of extensive morphological or molecular datasets [47][48][49][50] (see Ronquist's and others' reanalysis [51]). Rasnitsyn [43] suggested that insect flight originated from gliding [52].…”
Section: Geographical Isolation and 'Parallel Universes'mentioning
confidence: 99%